INSTITUTIONAL BRANDING IN THE DIGITAL ERA: HOW SOCIAL MEDIA MARKETING ACTIVITIES AND INFORMATION QUALITY SHAPE SCHOOL IMAGE IN INDONESIAN SENIOR HIGH SCHOOLS - Rudini Kusnadi; Arus Reka Prasetia (JIMBIEN: JURNAL MAHASISWA MANAJEMEN, BISNIS, ENTREPRENEURSHIP, 2026)
Digital transformation has reshaped how educational institutions communicate value, build stakeholder trust, and manage public perception. In Indonesia’s highly connected digital environment, senior high schools face increasing pressure to manage institutional visibility and information credibility strategically. This study develops a visibility-credibility framework to explain how Social Media Marketing Activities and Information Quality jointly contribute to school image, extending existing brand equity and information quality perspectives beyond their conventional treatment as separate antecedents. Using a qualitative conceptual research design, this study applies an integrative, framework-based literature review supported by secondary data from peer-reviewed publications, academic books, government statistics, institutional reports, and credible digital reports published primarily between 2016 and May 2026, while retaining earlier seminal works as theoretical foundations. Thematic analysis was employed to synthesize conceptual patterns across Social Media Marketing Activities, Information Quality, and school image. The findings propose that Social Media Marketing Activities strengthen school image through entertainment, interaction, trendiness, customization, and word of mouth as the visibility pathway, while Information Quality strengthens school image through accuracy, relevance, timeliness, completeness, and credibility as the trust pathway. A strong school image emerges when engaging digital communication is aligned with credible information, as visibility without credibility produces a fragile image, whereas credibility without visibility may leave institutional value unrecognized. This study contributes to digital marketing and educational branding literature by extending these perspectives to the underexplored context of Indonesian secondary education and provides a structured basis for ethical, engaging, and trustworthy digital branding strategies.